(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2023)
In the following paper, several questions will be raised. On the one hand, the relationship between climate change and the agricultural sector will be reviewed, taking into account that we are dealing with an activity that has two faces: both as a GHG emitter and as a CO2 sink. On the other hand, how this sector, through its practices, has become the guarantor of people’s health, given that it is also the guarantor of a sufficient, healthy and sustainable diet. Finally, another undoubted -and increasingly urgent- role of this sector as a revitalizer of the rural world will be recognized.